PENGARUH MARKETING, NILAI TAKSIRAN DAN BIAYA TITIP PADA GADAI EMAS TERHADAP MINAT NASABAH MENGGUNAKAN FASILITAS GADAI EMAS DI PT. BANK SYARIAH MANDIRI KCP TUBAN - Karomatun Ni'mah; Joko Hadi Purnomo; Niswatin Nurul Hidayati (LP2M Universitas Ibrahimy, 2020)
The main problem in this thesis is whether there is an influence of marketing, appraised value and entrusted cost in increasing customer interest in using the gold pawning facility at PT. Bank Syariah Mandiri KCP Tuban. This research is a type of quantitative research. Collecting data in this study is by distributing questionnaires to gold pawning active customers as many as 32 people, interviews and documentation with Pawning Staff. The technique used is Purposive Sampling, analyzed using Validity Test, Reliability Test, Multiple Linear Regression, Classic Assumption Test, F-count test and partial t test. The results obtained from this study indicate that marketing (X1) has a positive and significant effect on customer interest in using the gold pawning facility. With a t value of 3.054 with a significance level of 0.005 below alpha 5%, the beta value in the Unstandardized Coefficient shows a figure of 2812,565. This means that if the marketing activities undertaken by pawning staff are increased again, this will increase customer interest in using the gold pawning facility assuming other independent variables are considered constant. The appraised value does not affect the customer's interest in using the gold pawning facility, with a t value of 0.635 above 5% alpha. And the cost of deposit has a positive effect on customer interest in using the pawn facility, with a t value of 4.137 and a significance level of 0.000 below alpha 5%, the beta value in the Unstandardized Coefficient shows a figure of 391,547. This means that the costs of being entrusted to the gold pawning facility at PT. Bank Syariah Mandiri KCP Tuban, the cheaper it will attract customers to use the gold pawning facility. Variables X1, X2, X3 simultaneously influence customer interest in using the gold pawning facility at PT. Bank Syariah Mandiri KCP Tuban.